Transforming Work : Missiological Perspectives for the Church in the World - Cronshaw, Darren; Kappelhoff, Marguerite; Taylor, Steve (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2024)
Transforming Work offers a radical re-orientation of the nature and future of work and implications for mission. In conversation with David Bosch's Transforming Mission and other global and ecumenical voices, 21 leaders offer their vision for transforming the world of work and revisioning work to offer a transforming gift to the world. Writing from biblical and historical perspectives, with case studies and cultural exegesis, they explore work and leisure, ethics and economics, technologies and Artificial Intelligence. It is time to discern where God is transforming work in our cities and farms, shops and classrooms, politics and agencies.